Ancient water supports today's energy needs. Issue 5 (23rd May 2017) - D'Odorico, Paolo; Natyzak, Jennifer L.; Castner, Elizabeth A.; Davis, Kyle F.; Emery, Kyle A.; Gephart, Jessica A.; Leach, Allison M.; Pace, Michael L.; Galloway, James N.
Abstract: The water footprint for fossil fuels typically accounts for water utilized in mining and fuel processing, whereas the water footprint of biofuels assesses the agricultural water used by crops through their lifetime. Fossil fuels have an additional water footprint that is not easily accounted for: ancient water that was used by plants millions of years ago, before they were transformed into fossil fuel. How much water is mankind using from the past to sustain current energy needs? We evaluate the link between ancient water virtually embodied in fossil fuels to current global energy demands by determining the water demand required to replace fossil fuels with biomass produced with water from the present. Using equal energy units of wood, bioethanol, and biodiesel to replace coal, natural gas, and crude oil, respectively, the resulting water demand is 7.39 × 10 13 m 3 y −1, approximately the same as the total annual evaporation from all land masses and transpiration from all terrestrial vegetation. Thus, there are strong hydrologic constraints to a reliance on biofuel energy produced with water from the present because the conversion from fossil fuels to biofuels would have a disproportionate and unsustainable impact on the modern water. By using fossil fuels to meet today's energy needs, we are virtually using water from a geological past. The water cycle is insufficient to sustain the production of the fuel presently consumed by human societies. Thus, non‐fuel‐based renewable energy sources are needed to decrease mankind's reliance on fossil fuel energy without placing an overwhelming pressure on global freshwater resources. Key Points: Water virtually embodied in fossil fuels that is annually "burnt" with them exceeds global evapotranspiration from terrestrial land masses The energy that fueled the industrial revolution and is powering modern societies relies on water borrowed from an ancient past Water cycle would not be able to sustain current energy needs. "We" are using ancient water that will not be available to future generations Plain Language Summary: We investigate the water footprint of fossil fuels, accounting also for the water that was consumed for the production of the biomass that contributed over geological times to the formation of fossil fuels. We find that the water virtually embodied in fossil fuels that is annually "burnt" with them exceeds the global evapotranspiration from terrestrial land masses. Thus, the water cycle would not be able to sustain the current energy needs of human societies. Thus, the energy that fueled the industrial revolution and is powering modern societies relies on water borrowed from an ancient past, and that will not be available to future generations, similarly to the ongoing depletion (mining) of groundwater in many regions of the world. These results highlight the need to identify non‐fuel based forms of renewable energy.